Analysis of Patient Safety Management Implementation Towards the Occurrence of Post-Tooth Extraction Infection in Oral Surgery Clinic at RSGM IIK Bhakti Wiyata Kediri - Sih Winarti; Yuly Peristiowati; Sandu Siyoto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
The holy principles of pests and surgical principles are required when action is taken. Bacterial infection is one of the most common and most frequent complications. In the revocation action of RSGM IIK Bhakti Wiyata Kediri put patient safety as the main priority in health service. Post-tooth extraction infection may occur because the equipment and room are not sterile, the operator does not follow the existing SOP, inappropriate drug administration and the patient's own condition. The purpose of the study is to analyze the implementation of patient safety management on post-tooth extraction infection of Oral Surgery patients at RSGM IIK Bhakti Wiyata Kediri. Method used in this research is quantitative, Descriptive Observational as the process of data collection using Transversal Study design (Cross Sectional). The population of 112 person was taken at the oral surgery clinic of RSGMP IIK Bhakti Wiyata Kediri from 18 January to 18 February 2018. All the respondents were observed and examined from preparation of tooth extraxtion to control. The sampling technique used is Random Sampling by lottery technique By using Slovin formula, error rate of 2% obtained 107 samples. The result of multiple linear correlation analysis was obtained by equipment patient safety (0) (p-value = 0,000 <α = 0,05), place extraction patient safety (X2) (p-value = 0,000 <α = 0,05) (p = 0,401> α = 0,05) post-extraction instruction (X4) (p = 0,007 <α = 0,05). There is significant influence of patient safety of equipment (X1), place extraction patient safety (X2 and tooth extraction instruction, while tooth-extraction operator (X3) ) (p-value = 0.401> α = 0.05) had no significant effect on post-tooth extraction infection.R square value of 38 , 5%, means that the influence of the 4 variables is 38.5%, and the rest explained other variables that are not studied in this study. It is found that post-tooth extraction infection after the control is 17.8% .The most dominant influence is place extraction variable.